Investigation of the relationship between the cycle performance and the electronic structure in LiAlxMn2−xO4 (x = 0 and 0.2) using soft X-ray spectroscopy. Issue 25 (14th June 2017) - Asakura, Daisuke; Nanba, Yusuke; Makinose, Yuki; Matsuda, Hirofumi; Hosono, Eiji
Abstract : We found that the charge-transfer effect from the O 2p to Mn 3d orbitals is closely connected with the cycle performances for LiMn2 O4 cathode. Abstract : Al doping into LiMn2 O4 is one of the well-known methods to improve the cycle performance of the LiMn2 O4 cathode. We carried out soft X-ray emission spectroscopy (XES) for LiMn2 O4 and LiAl0.2 Mn1.8 O4 to elucidate the relationship between the Mn 3d electronic structures and cycle performances. After the first cycle, the XES spectra of LiAl0.2 Mn1.8 O4 are almost unchanged compared to the initial state. In contrast, charge-transfer excitation for the XES of LiMn2 O4 is significantly reduced, indicating that the Mn 3d-O 2p hybridization in LiMn2 O4 should be easily weakened by charge–discharge. In LiAl0.2 Mn1.8 O4, the Mn–O bond becomes more stable due to the decrease of Mn 3+ ions with Jahn–Teller distortion by Al 3+ doping, resulting in the improved cycle performance.